2019
DOI: 10.1523/jneurosci.2496-18.2019
|View full text |Cite
|
Sign up to set email alerts
|

STIM1 Is Required for Remodeling of the Endoplasmic Reticulum and Microtubule Cytoskeleton in Steering Growth Cones

Abstract: The spatial and temporal regulation of calcium signaling in neuronal growth cones is essential for axon guidance. In growth cones, the endoplasmic reticulum (ER) is a significant source of calcium signals. However, it is not clear whether the ER is remodeled during motile events to localize calcium signals in steering growth cones. The expression of the ER-calcium sensor, stromal interacting molecule 1 (STIM1) is necessary for growth cone steering toward the calcium-dependent guidance cue BDNF, with STIM1 func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 100 publications
2
35
0
Order By: Relevance
“…One possibility is that microtubules deliver components necessary for stabilization of adhesion complexes (Kaverina et al, 2002). Another possibility is that microtubule entry promotes advance of smooth endoplasmic reticulum (SER) and that interaction with the adhesion complex stabilizes both the dynamic microtubules and the SER (Dailey and Bridgman, 1989; Pavez et al, 2019; Zhang and Forscher, 2009). These possibilities are not mutually exclusive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One possibility is that microtubules deliver components necessary for stabilization of adhesion complexes (Kaverina et al, 2002). Another possibility is that microtubule entry promotes advance of smooth endoplasmic reticulum (SER) and that interaction with the adhesion complex stabilizes both the dynamic microtubules and the SER (Dailey and Bridgman, 1989; Pavez et al, 2019; Zhang and Forscher, 2009). These possibilities are not mutually exclusive.…”
Section: Discussionmentioning
confidence: 99%
“…However, microtubule dynamics also correlate with growth cone movement (Sabry et al, 1991; Tanaka and Kirschner, 1991), initial neuronal polarization (Witte et al, 2008) and are required for turning (Buck and Zheng, 2002). Bulk advance of microtubules correlates with neurite elongation (Athamneh et al, 2017) and microtubule associated proteins have been implicated in steering (Pavez et al, 2019). In addition, it has been shown that microtubules or microtubule-based motors can be manipulated to influence turning even when actin dynamics are unperturbed (Challacombe et al, 1997) (Buck and Zheng, 2002; Kahn and Baas, 2016; Nadar et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Regulation of ER-Ca 2+ release channels KD: decreased axonal length (Tsai et al, 2015) LOF: impaired anterograde transport (Tsai et al, 2015) AD (Mishina et al, 2008;Hedskog et al, 2013) ALS (Al-Saif et al, 2011;Prause et al, 2013) Chemotherapy-induced peripheral neuropathy (Bruna and Velasco, 2018) HD (Hyrskyluoto et al, 2013;Miki et al, 2015;Ryskamp et al, 2017) PD (Mishina et al, 2005;Mori et al, 2012) Spinal CMT (Li et al, 2015) spastin ER-Endosomes tethering MT severing LDs growth regulation KD: impaired axon outgrowth (Wood et al, 2006); reduced presynaptic area, increased excitatory junction potential amplitude, and accumulation of stabilized MTs (Trotta et al, 2004); loss of LDs (Papadopoulos et al, 2015); enhanced endosomal tubulation (Allison et al, 2013) LOF: reduced axonal length (Solowska et al, 2008); impaired regeneration (Stone et al, 2012); decreased presynaptic terminals size, decreased quantal content, and presynaptic loss of stabile MTs (Sherwood et al, 2004); large lysosomes (Allison et al, 2017) OE: reduced excitatory junction potential amplitude and presynaptic loss of stabile MTs (Trotta et al, 2004); increased LDs size and number (Papadopoulos et al, 2015) HSP (Hazan et al, 1999) STIM1 ER-PM tethering Regulation of ER-Ca 2+ uptake ER-MTs interaction KD: impaired presynaptic Ca 2+ influx and exocytosis (de Juan-Sanz et al, 2017) LOF/OE: impaired axon guidance (Shim et al, 2013) LOF: reduced ER translocation into growth cone filopodia (Pavez et al, 2019) AD (Gutierrez-Merino et al, 2018)…”
Section: Sigr1mentioning
confidence: 99%
“…In TACs, the tip of an ER tubule is attached to the tip of a MT plus end, through a complex containing the ER protein STIM1 and the MT-associated protein EB1. This binding leads to the ER tubule movement when the MT grows or retracts (Grigoriev et al, 2008;Pavez et al, 2019). The other mechanism mediating ER tubule movement along MTs, faster and more frequent than TAC, is ER sliding, driven by MT motor proteins such as kinesin-1 and dynein (Woźniak et al, 2009).…”
Section: Mt-mediated Tubular Er Dynamicsmentioning
confidence: 99%
“…Tse et al reported that SOCE-like activity in neurons derived from dissociated neurospheres of zebrafish [ 48 ]. Zebrafish Stim1 was shown to be crucial for the axon guidance of motor neurons and the regulation of calcium signaling [ 49 ]. We recently showed that the knockout of one orthologue of Stim2 , stim2b , caused hyperactivity and increased the susceptibility to seizures in zebrafish larvae [ 50 ].…”
Section: Introductionmentioning
confidence: 99%